Sustainable Building Retrofitting and Energy Efficiency - Nur IzieAdiana Abidin; Rozana Zakaria; Dodo Yakubu Aminu (Penerbit UTHM, 2021)
This book introduces various topics related to energy efficiency abd sustainable retrofitting. The topics cover researches and studies on the initiatives, strategies, reduction and improvements, application, effect and approach.Chapter 1 discussed the steps of retrofitting initiatives that can be implement to achieve building energy reduction. Retrofitting initiatives consists of three steps which are lean energy, green technology and clean energy. Chapter 2 focuses on giving an overview of green building assessment tools, the concept of retrofitting and retrofitting technologies. Chapter 3 discussed the building lighting energy simulation for retrofitting the Rest and Service Area (RSA) at Ayer Keroh Malaysia, which conducted using the Revit BIM model. Chapter 4 presents the prototyping of retrofitting strategies in the educational building to reuse a building type or building design. Chapter 5 reveals the strategies for mitigating the influence for modernism towards sustainable retrofitting of Hausa traditional palaces. Chapter 6 presenting the attitude towards energy consumption and strategies to encourage energy efficiency in a building. The energy consumption and occupant’s well-being besed on the retrofitting implemented in the office building at National Primary Health Care Development Agency Abuja were highlighted in Chapter 7. Chapter 8 reveals cool paint application to the indoor temperature conducted at the student hostel room in UTM presidential college. Lastly, Chapter 9 highlighted the passive design approach of building envelope for individual residents in achieving energyefficient building.